Reconciling marine and terrestrial evidence for post LGM ice sheet retreat in southern McMurdo Sound, Antarctica. (1st February 2017) - Anderson, Jacob T.H.; Wilson, Gary S.; Fink, David; Lilly, Kat; Levy, Richard H.; Townsend, Dougal
Abstract: Retreat of the Antarctic ice sheets since the Last Glacial Maximum (LGM) contributed to sea-level rise, but the location, amount, and timing of ice mass loss has been controversial. This paper presents new 10 Be exposure ages from glacially transported erratics which record post LGM retreat of grounded ice in the western Ross Sea. Ice elevation in southern McMurdo Sound was ≥520 m above present day sea level on the eastern side of Mount Discovery during the LGM, and the onset of major deglaciation in the region was after 14 ka. The ice surface lowered from ∼520 to 234 m above present day sea level between 14.0 ka and 10.3 ka and from 234 m to ∼30 m between 10.3 ka and 7.4 ka. This late-glacial and Holocene deglaciation chronology from southern McMurdo Sound is consistent with other records on the margins of the Ross Embayment, and implies that the western margins of the Ross Sea Ice Sheet (RSIS) experienced most mass loss during the early to middle Holocene. These 10 Be exposure ages coupled with sediment provenance define a two-stage ice flow scenario for McMurdo Sound subdividing differing reconstructions into an early and late phase. Prior to Termination I, an expanded Koettlitz Glacier flowed north and northeast between Brown Peninsula and Mount Discovery and coalesced with northward flowing ice fed from the Skelton and Mulock Glaciers. Thinning and retreat of the Koettlitz Glacier and perhaps other outlet glaciers flowing through the Royal Society Range allowed ice grounded in the Ross Sea to flow westward and northward, north of Brown Peninsula. Grounding-line recession in the Ross Sea during the late-glacial and Holocene was likely driven by Southern Ocean warming and sea-level rise from the retreat of the Northern Hemisphere ice sheets and the outer margins of the Antarctic ice sheets. Highlights: Process understanding of marine-based grounded ice behaviour in the western Ross Sea. Pattern and timing of retreat of grounded ice in southern McMurdo Sound over the past 14 ka. Two-stage ice flow reconstruction for McMurdo Sound during the last glacial cycle.